Body water conservation through selective brain cooling by the carotid rete: a physiological feature for surviving climate change? - Strauss, W.M.; Hetem, R.S.; Mitchell, D.; Maloney, S.K.; O’Brien, H.D.; Meyer, L.C.R.; Fuller, A. (Oxford University Press (OUP), 2017)
Some mammals have the ability to lower their hypothalamic temperature below that of carotid arterial blood temperature, a process termed selective brain cooling. Although the requisite anatomical structure that facilitates this physiological process, the carotid rete, is present in members of the Cetartiodactyla, Felidae and Canidae, the carotid rete is particularly well developed in the artiodactyls, e.g. antelopes, cattle, sheep and goats. First described in the domestic cat, the seemingly obvious function initially attributed to selective brain cooling was that of protecting the brain from thermal damage. However, hyperthermia is not a prerequisite for selective brain cooling, and selective brain cooling can be exhibited at all times of the day, even when carotid arterial blood temperature is relatively low. More recently, it has been shown that selective brain cooling functions primarily as a water-conservation mechanism, allowing artiodactyls to save more than half of their daily water requirements. Here, we argue that the evolutionary success of the artiodactyls may, in part, be attributed to the evolution of the carotid rete and the resulting ability to conserve body water during past environmental conditions, and we suggest that this group of mammals may therefore have a selective advantage in the hotter and drier conditions associated with current anthropogenic climate change. A better understanding of how selective brain cooling provides physiological plasticity to mammals in changing environments will improve our ability to predict their responses and to implement appropriate conservation measures.
Keywords: Artiodactyl success; brain temperature; carotid arterial blood temperature; osmoregulation; physiological plasticity; Rostral epidural rete mirabile